Enhanced Photoinduced Electron Transfer Through a Tyrosine Relay in a De Novo Designed Protein Scaffold Bearing a Photoredox Unit and a FeIIS4 Site. Issue 7 (8th April 2021) - Tebo, Alison; Quaranta, Annamaria; Pecoraro, Vincent L.; Aukauloo, Ally
Abstract: Electron transfer (ET) processes in biology over long distances often proceed via a series of hops, which reduces the distance dependence of the rate of ET. The protein matrix itself can be involved in mediating ET directly through the participation of redox‐active amino acids. We have designed an electron transfer chain incorporated into a de novo protein scaffold, which is capable of photoinduced intramolecular electron transfer between a photoredox unit and a Fe II S4 site through a tyrosine amino acid relay. The kinetics were characterized by nanosecond laser pulse photolysis and revealed that electron transfer from [Ru III bpymal] 3+ proceeds most efficiently via a tyrosine located ∼16 Å from Rubpymal (bpymal=1‐((1‐([2, 2′‐bipyridin]‐4‐yl)‐1H‐1, 2, 3‐triazol‐4‐yl)methyl)‐1H‐pyrrole‐2, 5‐dione). Removal of the tyrosine as the electron relay station results in a 20‐fold decrease in the apparent rate constant for the electron transfer. Abstract : Sharing is caring : We have designed an electron transfer chain incorporated into a de novo protein scaffold, which is capable of photoinduced intramolecular electron transfer between a photoredox unit and a Fe II S4 site through a tyrosine amino acid relay. The kinetics were characterized by nanosecond laser pulse photolysis and revealed that electron transfer from the photoredox unit [Ru III bpymal] 3+ proceeds most efficiently via a tyrosine located circa 16 Å from Rubpymal ((bpymal=1‐((1‐([2, 2′‐bipyridin]‐4‐yl)‐1H‐1, 2, 3‐triazol‐4‐yl)methyl)‐1H‐pyrrole‐2, 5‐dione)). Removal of the tyrosine as the electron relay station results in a 20‐fold decrease in the apparent rate constant for the electron transfer.